Formal and Stylistic Characteristics of Discourse Representation Modes in English Fiction - N. L. Baydikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
Formal and stylistic characteristics of the main discourse representation modes - direct, indirect and represented discourse - are considered. The comparative analysis of the Russian and English terminology of discourse representation modes is given. Formal indicators of direct, indirect and represented discourse are generalized and presented. When determining the stylistic status of discourse representation modes, the author denies the stylistic priority of represented discourse in comparison with two other discourse representation modes. It is asserted that all discourse representation modes have wide stylistic possibilities, realized by varying the formal and content characteristics of the narrator’s plane and that of the characters. The direct speech creates the effect of dynamism, naturalness, the reader's involvement in the story. It is proved that the indirect speech allows the narrator not only to represent the characters’ speech with different degrees of detailed elaboration, but also to express his attitude towards it. Particular attention is paid to the represented speech, which forces the reader to interpret the utterance himself due to its pragmatic ambiguity. The author confirms by examples that the represented discourse can create ambiguity not only of the narrative planes (those of the author or the characters), but also of the forms of speech (external or internal).